Assessment of indications of lower section caesarean section at tertiary care centre: a cross sectional study - Badge, Vijay L.; Aggarwal, Sumit Suresh; Ambalkar, Deepti D.; Humne, Arun; Raghuwanshi, Neethika (International Journal Of Community Medicine And Public Health, 2017)
Background: Caesarean section is one of the commonly performed surgical procedures in obstetrics and is certainly one of the oldest operations in surgery. One of the most dramatic features of modern obstetrics is the increase in the caesarean section rate. The present study was conducted to estimate proportion of various indications of LSCS and also to assess socio demographic profile of mothers undergoing caesarean section in a tertiary care centre. Methods: The present cross sectional observational study was conducted at Government Medical College & Hospital, Akola in the post natal ward (PNC). Non probability convenient sampling method was used. All patients admitted to PNC ward after LSCS were included in study. For data collection paper based pre tested, semi –structured questionnaire was used. Results: Previous LSCS was indication for LSCS in 32% cases. Eclampsia, preeclampsia and Anaemia were the indications for LSCS in 19.3%, 8.6% and 5.3% cases respectively. Other common indications includes CPD, meconium stained liquor, fetal distress, breech presentations, twin pregnancy and preterm labour. Conclusions: The proportion of LSCS is more than WHO recommended proportion of LSCS. It may be due to present institute acts as tertiary care center. Still this proportion is high, so encouragement should be given to trial of labour in selected low risk cases and in Primi patients whenever possible.